Serelaxin Treatment Reduces Oxidative Stress and Increases Aldehyde Dehydrogenase-2 to Attenuate Nitrate Tolerance - Leo, Chen Huei; Fernando, Dhanushke T.; Tran, Lillie; Ng, Hooi Hooi; Marshall, Sarah A.; Parry, Laura J. (Frontiers in Pharmacology, 2017)
Background: Glyceryl trinitrate (GTN) is a commonly prescribed treatment for acute heart failure patients. However, prolonged GTN treatment induces tolerance, largely due to increased oxidative stress and reduced aldehyde dehydrogenase-2 (ALDH-2) expression. Serelaxin has several vasoprotective properties, which include reducing oxidative stress and augmenting endothelial function. We therefore tested the hypothesis in rodents that serelaxin treatment could attenuate low-dose GTN-induced tolerance. Methods and Results: Co-incubation of mouse aortic rings ex vivo with GTN (10 µM) and serelaxin (10 nM) for 1 hour, restored GTN responses, suggesting that serelaxin prevented the development of GTN tolerance. Male Wistar rats were subcutaneously infused with ethanol (control), low-dose GTN+placebo or low-dose GTN+serelaxin via osmotic minipumps for 3 days. Aortic vascular function and superoxide levels were assessed using wire myography and lucigenin-enhanced chemiluminescence assay respectively. Changes in aortic ALDH-2 expression were measured by qPCR and Western blot respectively. GTN+placebo infusion significantly increased superoxide levels, decreased ALDH-2 and attenuated GTN-mediated vascular relaxation. Serelaxin co-treatment with GTN significantly enhanced GTN-mediated vascular relaxation, reduced superoxide levels and increased ALDH-2 expression compared to GTN+placebo-treated rats. Conclusions: Our data demonstrate that a combination of serelaxin treatment with low dose GTN attenuates the development of GTN-induced tolerance by reducing superoxide production and increasing ALDH-2 expression in the rat aorta. We suggest that serelaxin may improve nitrate efficacy in a clinical setting.